2021
DOI: 10.3389/fpsyg.2021.631179
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Indicators as a Tool for Diagnosis of Obesity and Other Health Risk Factors: A Literature Review

Abstract: Obesity is characterized by the accumulation of an excessive amount of fat mass (FM) in the adipose tissue, subcutaneous, or inside certain organs. The risk does not lie so much in the amount of fat accumulated as in its distribution. Abdominal obesity (central or visceral) is an important risk factor for cardiovascular diseases, diabetes, and cancer, having an important role in the so-called metabolic syndrome. Therefore, it is necessary to prevent, detect, and appropriately treat obesity. The diagnosis is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 210 publications
(287 reference statements)
1
66
0
10
Order By: Relevance
“…The Authors also stated that there was no specific cut-offs for VAT accumulation (Piqueras et al, 2021 ). Actually, the cut-off of 130 cm 2 of VAT has previously been defined by Hunter et al ( 1994 ) as associated with an increased risk of hypertension and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Authors also stated that there was no specific cut-offs for VAT accumulation (Piqueras et al, 2021 ). Actually, the cut-off of 130 cm 2 of VAT has previously been defined by Hunter et al ( 1994 ) as associated with an increased risk of hypertension and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Piqueras et al ( 2021 ) reported 17 indices or health indicators to assess obesity using non-invasive and low-cost anthropometric measurements, which constitute a good alternative to expensive and less accessible biomedical imaging.…”
Section: Additional Assessment Methods Of Obesitymentioning
confidence: 99%
See 3 more Smart Citations